LITERASI KEUANGAN SYARIAH TERHADAP PENGAMBILAN KEPUTUSAN TRANSAKSI PADA PERBANKAN SYARIAH - saputra, angga (Salam (Islamic Economics Journal), 2024)
ABSTRACTThe aim of this research is to determine the influence of Sharia Financial Literacy on Mudharabah Transaction Decision Making in Sharia Banking among High School Educators in Lampung Province. This research uses basic theory, namely Islamic financial literacy. This research uses primary and secondary data, namely reports on the number of high school teaching staff in Lampung Province who use mudharabah products at Bank Syariah Indonesia which were obtained directly from interviews and the official website of Bank Syraih Indonesia Lampung Province for the 2021-2022 period. The sampling process was carried out using the Slovin technique method. Based on the results of this research, it shows that the level of sharia financial literacy has a positive and significant effect on the decision to use sharia financial institutions.